THE SIMILAR MEANINGFUL WORDS BETWEEN IN EASTERN AND WESTERN COUNTRIES - Quvatova Mushtariy Farxodovna (TADQIQOTLAR.UZ, 2024)
Abstract: This article provides information about idoms,proverbs and phrases used in western and eastern countries. Mainly, there is talk about the similarity of these phrases, proverbs and idioms. That is, when and under what conditions they are used and how they affect humanity. It gives more information about how these expressions create emotional strength when used than a simple word.